Perineural Adductor Canal Catheter Placement for Prevention of Complex Regional Pain Syndrome-I Exacerbation After Knee Arthroscopy: A Case Report. Issue 4 (11th April 2022) - Calixto, Nathaniel E.; Saldanha, Usha
Abstract : Arthroscopic knee surgery is a common trigger for lower extremity complex regional pain syndrome (CRPS). Few studies assess nerve block catheters for CRPS treatment; they do not appear to be studies of regional anesthesia to treat CRPS that occurs after knee surgery. We present a case of CRPS-I triggered by knee surgery on multiple prior occasions but finally prevented by perineural adductor canal catheter placement. The literature presents only moderate evidence supporting interventions such as intravenous regional anesthesia and sympathetic blockade; continuous nerve blockade may be an effective treatment of CRPS-I and in particular postoperative CRPS-I.